2021
DOI: 10.1108/jrim-05-2020-0111
|View full text |Cite
|
Sign up to set email alerts
|

Influencers' intimate self-disclosure and its impact on consumers' self-brand connections: scale development, validation, and application

Abstract: PurposeThis study develops and validates a scale to measure social media influencers' intimate self-disclosure (SMIs' ISD), by accessing consumer perceptions of the intimacy levels of SMIs' self-disclosure. The authors further evaluate the extent to which SMIs' ISD fosters consumers' self-brand connections via consumer-SMI parasocial relationships.Design/methodology/approachThe scale was developed through item generation, purification, and validation. First, items were generated from existing scales and revise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 75 publications
(135 reference statements)
1
27
0
1
Order By: Relevance
“…Thirdly, consumers tend to have positive feelings for attractive anchors and transfer this positive attitude to commodities. Leite and Baptista (2021) suggests that online celebrity’s intimate self-disclosure to consumers will promote the attractiveness of its endorsement brands to consumers. The stronger the attraction of the anchor, the easier it is to establish a good interpersonal relationship with the consumers who watch the live stream, which is conducive to the audience’s love and identification with the anchor and their products.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Thirdly, consumers tend to have positive feelings for attractive anchors and transfer this positive attitude to commodities. Leite and Baptista (2021) suggests that online celebrity’s intimate self-disclosure to consumers will promote the attractiveness of its endorsement brands to consumers. The stronger the attraction of the anchor, the easier it is to establish a good interpersonal relationship with the consumers who watch the live stream, which is conducive to the audience’s love and identification with the anchor and their products.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Similarly, these factors may also manifest differently depending on the type of self-disclosure. A 2021 study showed that an influencer’s intimate self-disclosure (which resembles PSD) can strengthen consumers’ attitudes toward a brand, as mediated through PSI (Leite & Baptista, 2021). So too, PSD is an oft-used strategy to increase perceptions of a source’s authenticity (Gannon & Prothero, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, these scientists are engaging in different forms of self-disclosure, a strategy frequently employed by influencers (e.g., S. S. Lee & Johnson, 2022; Leite & Baptista, 2021), to share the “behind-the-scenes” of a scientist and to form relationships with their own followers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using social media platforms, endorsers can strategically interact with their audiences which serves to create richer associations (Lee and Eastin, 2021). Furthermore, by directly sharing contents of a more intimate nature, celebrities and influencers alike can create stronger personal and emotional bonds between themselves and followers (Leite and Buptista, 2021; Wang and Hu, 2021; Kim and Kim, 2022). This bond between celebrities and followers serves to enhance the cogency of endorsers (Knoll and Matthes, 2017), and consequently create richer celebrity associations which heighten the efficacy of the meaning transfer process from the celebrity to the brand (Schimmelpfennig and Hunt, 2020).…”
Section: Literature Review and Conceptual Modelmentioning
confidence: 99%